2020
DOI: 10.1259/dmfr.20200024
|View full text |Cite|
|
Sign up to set email alerts
|

Great potential of ultrasound elastography for the assessment of the masseter muscle in patients with temporomandibular disorders. A systematic review

Abstract: Objective: To summarize the available evidence on the use of elastography in the assessment of the masseter muscle in healthy individuals and patients with masseter muscle disorders. Methods: Systematic literature review has been performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Results: 16 of 142 studies identified were analyzed. Elastography was used in seven studies. Heterogeneity was observed in terms of study protocols, devices, patients, units of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…We analyzed data obtained from 140 healthy volunteers (74 men and 66 women) with a median age of 50 years (95% confidence interval (CI): 45.9-55). For women, the median The stiffness of the masseter muscle was measured with the Aixplorer Ultimate device (SuperSonic Imagine, Aix-en-Provence, France) using a high-frequency linear probe SL 18-5 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The obtained measurements were validated using the elasticity QA Phantom model 049A (Computerized Imaging Reference Systems, Inc, Norfolk, VA, USA).…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed data obtained from 140 healthy volunteers (74 men and 66 women) with a median age of 50 years (95% confidence interval (CI): 45.9-55). For women, the median The stiffness of the masseter muscle was measured with the Aixplorer Ultimate device (SuperSonic Imagine, Aix-en-Provence, France) using a high-frequency linear probe SL 18-5 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The obtained measurements were validated using the elasticity QA Phantom model 049A (Computerized Imaging Reference Systems, Inc, Norfolk, VA, USA).…”
Section: Resultsmentioning
confidence: 99%
“…Reports from the literature show that shear wave elastography has the potential to be used in the evaluation of the condition of masseter muscle stiffness [ 25 ]. Our study showed that chewing gum intensively increases the stiffness of both muscles of the masticatory system significantly.…”
Section: Discussionmentioning
confidence: 99%
“…We also recommend taking 3 separate measurements from 3 different images rather than, as was conducted in the present study, multiple measurements from 1 image. The method of measurement was modelled on previously published studies [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Masseter muscle stiffness was measured with shear-wave elastography before and immediately after the massage using the Aixplorer Ultimate device (SuperSonic Imagine, Aix-en-Provence, France) with a high-frequency linear probe SL 18–5 (5–18 MHz). On each examination, elastic Young's modulus was recorded, named in this study as an elasticity value and expressed in kPa [ 16 , 19 21 ]. The patients were examined in a supine, relaxed, and comfortable position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation